The fool of the world and the flying ship : a Russian folktale from the Skazki of Polevoi - Denise, Christopher (Philomel Books, 1994)
When the Czar proclaims that he will marry his daughter to the man who brings him a flying ship, the Fool of the World sets out to try his luck.